2021
DOI: 10.1111/petr.14096
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcome of early steroid withdrawal in pediatric renal transplantation

Abstract: Background: Steroid use in renal transplant is related to multiple adverse effects.Long-term effects of early withdrawal steroids in pediatric renal transplant were assessed.Methods: Renal transplant children with low immunological risk treated on basiliximab, tacrolimus, and mycophenolate with steroid withdrawal or steroid control were evaluated between 2003 and 2019. Clinical variables, treatment adherence, acute rejection, graft loss, and death were analyzed through hazard ratios, and Kaplan-Meier and multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
2
2
0
Order By: Relevance
“…At 3 years post-transplant, the majority of children had seen improvements in their height z-score with greater gains in prepubertal children. This is similar to data reported by Gajardo et al 47…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…At 3 years post-transplant, the majority of children had seen improvements in their height z-score with greater gains in prepubertal children. This is similar to data reported by Gajardo et al 47…”
Section: Discussionsupporting
confidence: 93%
“…At 3 years post‐transplant, the majority of children had seen improvements in their height z ‐score with greater gains in prepubertal children. This is similar to data reported by Gajardo et al 47 . showing significant improvement in the height z ‐score of 1.09 ± 0.82 at 3 years post‐transplant with steroid‐free maintenance immunosuppression compared to an z ‐score improvement of 0.11 ± 0.9 in the steroid‐based immunosuppression children ( p < .001).…”
Section: Discussionsupporting
confidence: 90%
“…Adolescence and young adulthood are considered critical periods with a high risk of graft loss due to bad adherence ( van Arendonk et al, 2013 ). Furthermore, previous studies in our center demonstrated that non-adherence was the main predictor of graft loss and death, turning immunosuppression monitoring into a primary priority to promote adherence in these patients ( Gajardo et al, 2021 ).…”
Section: Discussionmentioning
confidence: 98%
“…Alloimmunity is undoubtedly the pathophysiology of rejection. Rejection rates in pediatric populations are reported to be approximately 11% 58–60 in the first year after transplantation. However, the 1‐year rejection rate was 4% in our cohort, with a 5‐year rejection rate of 10%.…”
Section: Discussionmentioning
confidence: 99%